Prescription of antibiotics and knowledge about antibiotic costs among physicians working in tertiary-care hospitals. (December 2014) - Maltezou, Helena C.; Maltezos, Efstratios; Antoniadou, Anastasia; Gourgoulis, Georgios-Michael; Katerelos, Panos; Adamis, Georgios; Petrikkos, George; Gargalianos, Panagiotis
<x content-type="archive" xml:space="preserve">Abstract</x> The objective of this study is to investigate antibiotic prescription practices among hospital-based physicians in Greece, using the 2007 national guidelines as the golden standard. A total of 168 physicians participated. Compliance rate with the first-line antibiotic treatment recommended by the national guidelines was 65·5% for acute bacterial sinusitis; 24% for acute uncomplicated cystitis; 36·4% for an acute febrile diarrheic syndrome; 38% for an afebrile adult with chronic obstructive pulmonary disease and non-productive cough of 7 days duration; 23·2% for streptococcal pharyngotonsillitis; 55·1% for a surgically sutured, dirty wound; and 48·2% for community-acquired pneumonia. The total mean rate of compliance with the first recommended antibiotic was 41·2%.